Impact of ERM and Capital Structure on Firm Value in Indonesia: Dampak ERM dan Struktur Modal terhadap Nilai Perusahaan di Indonesia - Putri, Vera Ardana; Maryanti, Eny (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of enterprise risk management (ERM) and capital structure on firm value, with firm age and size as moderating factors, using data from 47 banking companies listed on the Indonesian Stock Exchange (2019-2021). Utilizing quantitative methods and Moderate Regression Analysis with SPSS, the results indicate that ERM does not affect firm value, while capital structure has a positive effect. Firm age weakens the impact of ERM but strengthens the effect of capital structure on firm value. Conversely, firm size enhances the impact of ERM but weakens the effect of capital structure. These insights are crucial for investors in the banking sector. Highlight: ERM does not significantly impact firm value. Capital structure positively influences firm value. Firm age and size moderate these effects. Keyword: enterprise risk management, capital structure, firm value, firm age, firm size